Pengaruh Keberagaman, Iklim Organisasi dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior - Arbiyanti, Rina; Sudibjo, Niko (Jurnal Manajemen, 2020)
Organizational Citizenship Behavior (OCB) is an individual voluntary behavior that indirectly brings benefit and success of an organization. High level of OCB shown by teachers in school may give positive contribution in maintaining school environment as welcoming place to learn and study. This study aims to determine the effect of diversity, organizational climate and organizational commitment on organizational citizenship behavior of teachers in XYZ School in Tangerang. This research is a quantitative approach using PLS SEM method. The research subjects were 46 respondents who work for this school. The results show that diversity, organizational climate, and organizational commitment have a positive effect on organizational citizenship behavior of teachers in the School.